(untitled) (RIAF. International Journal of Physical Activity, 2024)
One of the indicators of basketball players’ physical condition is power. Jump height is a good predictor of muscular power, and therefore, various types of vertical jumps have been employed as standardized tests of athletic performance. Objective. This research aims to describe and understand the power developed during the Squat Jump (SJ) among male basketball players from the Holguín team as they prepared to participate in the Superior League. Methods. To carry out the assessment, methods such as observation during training sessions and competitive matchups were used. Given the quantitative nature of the research, a pre-experimental design was chosen, with a non-probabilistic sample of 21 basketball players. For data analysis, descriptive statistics were applied, using median and standard deviation as measures of central tendency, processed through SPSS 0.22. The tools used included the contact mat for the Bosco test, which provided values such as the maximum absolute power of the best SJ jump and relative maximum power. Results. It was found that forwards and centers were the positions that generated the greatest power during the jump test, unlike players in the guard position. This led to new strategies for improving explosive strength in the lower limbs. Conclusions. The research on the SJ in basketball proved strategic for the planning of training loads according to playing positions in basketball. It undoubtedly contributes to deepening our understanding of power preparation in vertical jumps, aiming for improved athletic performance.